ANALISA KEPUASAN PENGGUNA WEBSITE TOP UP VOUCHER GAMES ONLINE MENGGUNAKAN WEBQUAL 4.0 - Oktaviana R, Shinta; Prayudha, Rifqi Avriyansyah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
The online gaming industry generates revenue through the sale of games that customers pay to play. In Indonesia, there are numerous programs that offer online game vouchers at different costs and with various payment options. The objective of this study is to identify the variables that influence user satisfaction on web applications that offer online game coupons. The study used the WebQual 4.0 methodology as a tool for evaluating the caliber of web apps. The research was conducted online via the Google Form application. The data collection period spanned from June 11, 2023 to June 29, 2023, and we got 130 respondents. The data was evaluated using descriptive statistical analysis with the aid of SPSS tools. The findings of this study indicate that the variable of Interaction Quality (X3) has a significant role in determining user satisfaction for online game voucher websites, however the factors of Usability (X1) and Information Quality (X2) do not exert any influence on user satisfaction. Therefore, this research shows that hypotheses H1 and H2 are rejected for all data groups. This research provides recommendations to online game voucher application owners to focus on interaction quality variables in further web application development.